Long-term fertility experiments for irrigated rice in the West African Sahel: Effect on macro- and micronutrient concentrations in plant and soil - Haefele, S.M.; Thomas, C.L.; Saito, Kazuki (Elsevier, 2022)
Little is known about the impact of long-term intensive irrigated rice cropping on secondary macro and micronutrients in soils and crops. Therefore, the present study analysed the effect of intensive irrigated rice cropping on nutrient concentrations in soils and rice (grain and straw at harvest) in two long-term experiments that were established in 1991 for intensive rice-based irrigated systems in the Senegal River valley at Ndiaye and Fanaye, Senegal. The experiments included six different fertilizer treatments and rice was grown for two seasons per year. The samples were collected in the 2016/17 dry season (26 years or 52nd continuous rice cropping season after the establishment). Average grain yields from 1991 to 2016/17 for the different fertilizer treatments indicate that yield was limited by N and P at both sites. At Ndiaye, 120 kg N ha−1 seemed sufficient to reach highest achievable yields, whereas 180 kg N ha−1 was necessary at Fanaye. Soil organic carbon and total soil N did increase considerably over the full length of the experiment at both sites and in all treatments even though all crop residues were removed every season. The estimated increase in total topsoil N (across all fertilizer treatments) per season was 10.8 and 11.4 kg N ha−1 at Ndiaye and Fanaye, respectively. Fertilizer treatments differed in their N, P and K rate but significant effects on total soil concentrations were only detected for P. Using the Mehlich3 soil test, we analysed treatment effects on available P, K, Ca, Mg, S, Mn, Zn and Fe. Critical Mehlich3 values from the literature indicated likely P limitation at both sites and in all but one treatment (high PK treatment), a starting but minor K limitation at Fanaye, a strong S limitation at Fanaye, and a minor Zn limitation at Fanaye and Ndiaye. These indications were mostly confirmed by the grain and straw analysis but with the exception of the P limitation, the actual effect of these possible nutrient limitations on production would need to be tested with targeted field experiments. We conclude that continuous rice cultivation in the Sahel for 26 years can be sustained and even increases soil organic carbon and total soil nitrogen. However, in addition to the common N and P deficiencies, likely deficiencies of K, S and Zn are appearing and may begin to limit rice yields in intensive systems in Africa. The Mehlich3 test seems an efficient tool to identify such deficiencies in irrigated rice soils.